2022
DOI: 10.3390/rs14194865
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Microphysical Characteristics of Fog at a Northern Airport in Alberta, Canada

Abstract: Reduction in visibility (Vis) due to fog is one of the deadliest severe weather hazards affecting aviation and public transportation. Nowcasting/forecasting of Vis reduction due to fog using current models is still problematic, with most using some type of empirical parameterization. To improve the models, further observational studies to better understand fog microphysics and seasonal variability are required. To help achieve these goals, the seasonal and microphysical characteristics of different fog types a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Advection fog (AF), or moist, occurs when warm air is flowing over water with different temperatures. This type occurs frequently in coastal regions, as an example is shown in [7], results showed that radiation fog dominates at CYOD (Colt Lake airport) in summer while precipitation, advection and cloud-base-lowering fog mostly occur in fall and winter.…”
Section: Introductionmentioning
confidence: 87%
“…Advection fog (AF), or moist, occurs when warm air is flowing over water with different temperatures. This type occurs frequently in coastal regions, as an example is shown in [7], results showed that radiation fog dominates at CYOD (Colt Lake airport) in summer while precipitation, advection and cloud-base-lowering fog mostly occur in fall and winter.…”
Section: Introductionmentioning
confidence: 87%
“…Its measurement range of droplets is 2 µm-50 µm. So far, FM120 has been widely used in alpine stations for detection of meteorological parameters [56][57][58]. The schematic of the working function of FM120 is shown in Figure 5.…”
Section: The Fog Monitor (Fm120)mentioning
confidence: 99%
“…This information is used as a guideline for estimating aircraft holdover time and de-icing operation [35]. In the guidance table, the Vis data are also segregated according to daytime and nighttime conditions [35], and this issue is discussed extensively in the previous studies [4,36,37]. According to Boudala et al, (2012), the nighttime visibility (V n ) can be related to daytime visibility (V d ) as…”
Section: Visibility and Solid Precipitation Intensity Data Analysismentioning
confidence: 99%